2016
DOI: 10.4103/0976-3147.168435
|View full text |Cite
|
Sign up to set email alerts
|

How do repeat suicide attempters differ from first timers? An exploratory record based analysis

Abstract: Background:Evidence indicates that repeat suicide attempters, as a group, may differ from 1st time attempters. The identification of repeat attempters is a powerful but underutilized clinical variable.Aims:In this research, we aimed to compare individuals with lifetime histories of multiple attempts with 1st time attempters to identify factors predictive of repeat attempts.Setting and Design:This was a retrospective record based study carried out at a teaching cum Tertiary Care Hospital in South India.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In contrast to the findings of Pompili et al (2011), our results did not indicate that the number of stressors precipitating death by suicide varied depending on suicide attempt history. However, these findings are consistent with other studies in suicide attempters (e.g., Menon et al, 2016). Our finding that those who died on a first attempt experienced a less intense stressor prior to death by suicide is also consistent with the results reported by Pettit and colleagues (2004) – this study found that the number of suicide attempts was significantly and positively associated with level of stress precipitating the attempt.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the findings of Pompili et al (2011), our results did not indicate that the number of stressors precipitating death by suicide varied depending on suicide attempt history. However, these findings are consistent with other studies in suicide attempters (e.g., Menon et al, 2016). Our finding that those who died on a first attempt experienced a less intense stressor prior to death by suicide is also consistent with the results reported by Pettit and colleagues (2004) – this study found that the number of suicide attempts was significantly and positively associated with level of stress precipitating the attempt.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Menon and colleagues (2016) found individuals with multiple previous attempts to have higher levels of hopelessness in comparison to those with only one previous attempt. Thus, future studies should investigate if and how these findings may relate to populations of suicide decedents.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although there were significant differences in suicide methods, using pesticide or other poisons were still the most common methods of suicide (Menon et al, 2016), which was contrary to the findings that one fifth of suicide repeaters attempted subsequent suicides with more violent and lethal methods such as hanging and jumping from height (Pompili et al, 2011). Repeated attempters were found to maintain highly lethal methods in the following fatal attempts (Chen et al, 2016; Pan et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…There have been many studies supporting close connection between mental disorders such as mood disorder, psychotic disorder, adjustment disorder, substance abuse, etc., and suicide attempts (Menon et al, 2016; Pagura et al, 2008). The rate of mental disorders in suicide attempters (10%) was much lower compared to those found in western countries, of which, sometimes can be as high as 80–90%.…”
Section: Discussionmentioning
confidence: 99%
“…The Association between Neuroticism and Re-Attempted Suicide compared to single attempters [11,19]. Previous research have shown that certain personality traits like neuroticism appear to be associated with increased suicide risk of completed suicide [24].…”
Section: Research Articlementioning
confidence: 99%